Perfil profissional, formação e tecnologia leve no trabalho de profissionais médicos e enfermeiros da atenção primária à saúde no município de Guarujá, S.P. - Gleriano, Josué Souza (2014)
Introduction: The intersection between health, education and work permeates the institutionalization of the NHS since its proposed construction. The professional health education leads to permanent health education and the centrality of care practices and technologies. The axis training to practice and practice to the service becomes the object of this study. Objective: To characterize the profile of doctors and nurses working in health units belonging to the Primary Care of Guarujá SP Method: This was a study approved by the Ethics and Research Committee No. 452 727 / CEP UNAERP / 2013 prepared by A cross-sectional study. Participating physicians and nurses in health centers were to link the level of Primary Health, who were not on vacation or away for health reasons, answering a self-administered structured questionnaire developed by Brazil Telehealth and was drafted by a complementary conducted a descriptive analysis of all variables of the study. A descriptive analysis of all variables of the study was conducted. Qualitative variables were presented in terms of their absolute and relative values. Quantitative variables in terms of their values of central tendency and dispersion. To evaluate the association between categories of health professionals (doctors, nurses) and qualitative variables the Chi-square and Fisher's exact test was used. For quantitative variables, the normality and homogeneity of variances were assessed using Kolmogorov-Smirnov and Levene tests, respectively. As these two variables were not satisfied principles, the nonparametric Mann-Whitney U test was used. The significance level was 5%. Statistical package used was SPSS for Windows 17.0. Results: In relation to the research subjects shows that the professionals linked to units of family health were more accepted to participate. Regarding age, one realizes that professional family health (USAFA) are younger than those of basic health units (BHU) (p <0.05) sequence that also references the type of employment in the city. Regarding the type of employment shows that the higher prevalence in the APS will occur by CLT (p <0.05). The satisfaction expressed by health professionals when analyzed in the context of increased prevalence is a good level, highlighting only with respect to the health service system of the municipality which is rated as fair (p <0.05). Regarding the light for the job-analysis technologies in general feels empowered to play a familiar approach, community, the multidisciplinary work group activities and home visits (p <0.05). Conclusion: The knowledge of the profile of professional members of the body of human resources in health services points need qualification, first exposed in continuing education scenario and lack of introductory courses and approaches to the labor process in APS. The scenario might propose in relation to working technologies then requested the validation of professional a weakness in what is expected for the level of attention. The stability of the employment relationship must be worked with professionals especially in relation to the supervision of labor and production for the attention, remembering that the spaces of care are not just specific to a pathological clinical look. The reflection of the expanded clinic should be treated, in question, as a human resources policy not only to UBS.